Spiritual and psychological well-being among theology faculty students: An examination of interrelationships and predictive factors - Yetiş, Hatice; Esgin, Ali (Universitas Negeri Padang, 2023)
This study examines the relationship between spiritual well-being and psychological well-being among theology faculty students. Spiritual well-being refers to the positive values associated with self-identity, social environment, religious and non-religious symbols, the meaning of life, and personal satisfaction, while psychological well-being involves being in harmony with others, having self-respect and confidence, enjoying life, and effectively dealing with problems. These two states of well-being are interconnected and mutually influential. A correlational model was used to investigate the levels of spiritual well-being and psychological well-being among the participants and explore whether these levels vary based on demographic factors. The study aimed to determine the relationship between spiritual well-being and psychological well-being and assess the extent to which psychological well-being predicts spiritual well-being. Data were collected from 307 theology faculty students in Istanbul and Izmir using the PERMA Well-Being Scale, Spiritual Well-Being Scale, and a Personal Information Form. Statistical analysis was performed using SPSS 24.0, including calculating scale scores and examining kurtosis and skewness coefficients to assess score distribution. The findings revealed positive relationships between the variables, and it was determined that psychological well-being significantly predicted spiritual well-being. Based on these results, the study provides recommendations for further research and practice.